Niobium-titanium-silicon-carbon composite material, preparation method and application thereof, and battery

By using niobium titanium silicon carbon composite material as the negative electrode material in lithium-ion batteries, the problem of poor rate performance and cycle performance of silicon materials is solved, and the high rate specific capacity and cycle life of the battery are significantly improved, meeting the needs of high energy density and long-term stable power supply.

CN119674010APending Publication Date: 2025-03-21无锡锂凰科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411864823.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When silicon material is used as the negative electrode material in lithium-ion batteries, its rate performance and cycle performance are poor, resulting in a sharp decline in the battery's capacity in high-rate charging and discharge scenarios, shortening the cycle life, and unable to meet the needs of high energy density and long-term stable power supply.

Method used

By coating porous niobium oxide Nb2O5-x particles in the silicon-based negative electrode material, and introducing solid electrolytes and nanoporous lithium titanium oxides, a niobium titanium silicon carbon composite is constructed to enhance ion/electron transport capacity, reduce the destructive stress caused by silicon expansion, and improve the battery's magnification capacity and cycle life.

Benefits of technology

The excellent rate performance and cycle performance of niobium titanium silicon carbon composite materials in the negative electrode materials of lithium-ion batteries has been achieved, which significantly improves the high rate specific capacity and cycle life of the battery, and meets the needs of high energy density and long-term stable power supply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674010A_ABST
    Figure CN119674010A_ABST
Patent Text Reader

Abstract

The invention discloses a niobium-titanium-silicon-carbon composite material, a preparation method and application thereof and a battery. The preparation method of the niobium-titanium-silicon-carbon composite material comprises the following steps: mixing porous niobium oxide, a silicon source and a solid electrolyte to obtain a silicon intermediate product; and granulating and screening the mixture of the silicon intermediate product, the nano-porous lithium titanate oxide and the carbon source to obtain the niobium-titanium-silicon-carbon composite material. The niobium-titanium-silicon-carbon composite material prepared by the invention shows excellent rate capability and cycle performance when being used as a battery negative electrode material, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a niobium-titanium-silicon-carbon composite material and a preparation method, application and battery thereof. Background Art

[0002] With the rapid development of modern electronic devices and the booming new energy vehicle industry, the demand for high-performance energy storage batteries is becoming increasingly urgent. Lithium-ion batteries are widely used in many fields due to their high energy density, long cycle life and other advantages. However, the theoretical specific capacity of traditional graphite negative electrode materials is relatively low (about 340-370mAh / g), which is difficult to meet the growing demand for high energy density batteries. Silicon materials are regarded as the most promising next-generation lithium-ion battery negative electrode materials because of their ultra-high theoretical specific capacity (up to 4200mAh / g).

[0003] However, silicon materials face many severe challenges in practical applications. In terms of rate performance, silicon has poor conductivity and low electron transfer rate during the charge and discharge process. When the battery is in a high-rate charge and discharge condition, it cannot respond to the rapid migration of electrons in time, resulting in a significant increase in the internal resistance of the battery and serious polarization. As a result, the capacity of the battery at high rates decays sharply and cannot output enough power, which seriously limits its application in scenarios that require rapid charge and discharge, such as fast charging of electric vehicles and high-power electronic devices. In terms of cycle performance, silicon will produce a huge volume expansion effect during the insertion and extraction of lithium ions, which can reach 300% or even higher. This large volume change will destroy the structural integrity of the silicon negative electrode material, causing the electrode material to pulverize and fall off, resulting in poor electrical contact between the electrode and the current collector, reduced utilization of active materials, and continuous increase in the internal resistance of the battery, which ultimately causes a significant shortening of the battery cycle life. After several charge and discharge cycles, the capacity retention rate drops significantly, which cannot meet the requirements of long-term stable power supply, greatly hindering the large-scale promotion and application of silicon negative electrode materials in commercial lithium-ion batteries. Therefore, it is urgent to develop a technical solution that can effectively improve the rate performance and cycle performance of silicon materials. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the defects of the silicon material in the prior art in that the rate performance and cycle performance are poor when used as the negative electrode material of lithium batteries, and provide a niobium-titanium-silicon-carbon composite material and its preparation method, application and battery. The niobium-titanium-silicon-carbon composite material prepared by the present invention exhibits excellent rate performance and cycle performance when used as the negative electrode material of the battery, and the preparation method is simple.

[0005] The present invention first coats porous niobium oxide Nb2O on a silicon-based negative electrode material. 5-x Particles, defect-rich Nb2O prepared by etching 5-xNanoporous material particles promote the electrolyte to enter the material through nanopores, + The diffusion distance is greatly reduced, and the ability to retain electrolyte is enhanced to improve the cycle life; the introduction of defect states increases the ion / electron transport capacity, thus having ultra-high rate and high capacity characteristics; combined with solid electrolyte coating, the lithium ion transport capacity of the silicon interface can be enhanced, greatly improving the rate capacity and cycle life of silicon materials; finally, through Nb2O 5-x The rigid and flexible low elastic modulus structure of nanoporous materials suppresses the destructive stress caused by silicon expansion and improves the stability of silicon negative electrode materials. In addition, when silicon negative electrode materials and carbon materials such as graphite are mixed to prepare silicon-carbon negative electrode materials, adding a small amount of nanoporous lithium titanate oxides with lower costs can enhance the ion transport performance of the graphite surface and the graphite / silicon interface, further construct fast ion transport channels, and enhance rate performance.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing a niobium-titanium-silicon-carbon composite material, comprising the following steps:

[0008] Porous niobium oxide, a silicon source and a solid electrolyte are mixed to obtain a silicon intermediate product; then the mixture of the silicon intermediate product, nanoporous lithium titanate oxide and a carbon source is granulated and sieved to obtain the niobium-titanium-silicon-carbon composite material.

[0009] In the present invention, the porous niobium oxide preferably has a defective structure. The chemical formula of the porous niobium oxide may be Nb2O 5-x , wherein 0≤x<1. The pore size of the porous niobium oxide is preferably 1-15 nm, more preferably 2-5 nm, such as 2.4 nm, 3 nm or 4 nm.

[0010] In the present invention, the method for preparing the porous niobium oxide preferably comprises the following steps:

[0011] (a) subjecting a mixture of lithium niobate and an acid to a hydrothermal reaction at 110-150° C. for 1-5 hours, washing and drying to obtain a niobium precursor;

[0012] (b) Under the protection of an inert gas, calcining the niobium precursor at 400-900° C. for 0.5-6 h to obtain the porous niobium oxide.

[0013] The acid may be one or more of hydrochloric acid, sulfuric acid and phosphoric acid. The concentration of the acid may be 0.5-2M, for example 1M.

[0014] In a specific embodiment, the acid is 1M hydrochloric acid.

[0015] Wherein, the mass ratio of the lithium niobate to the acid may be (10-30):1, such as 15:1, 20:1 or 25:1.

[0016] The temperature of the hydrothermal reaction is preferably 120-140° C., such as 130° C. The time of the hydrothermal reaction is preferably 1-3 h, such as 1 h.

[0017] The washing operation and conditions may be conventional in the art, for example, deionized water is generally used for washing.

[0018] The inert gas may be conventional in the art, such as argon or nitrogen.

[0019] The calcination temperature is preferably 700-900° C., such as 800° C. The calcination time is preferably 4-6 hours, such as 5 hours.

[0020] In the present invention, the silicon source may be one or more of elemental silicon, silicon monoxide, silicon dioxide, silicon alloy, porous silicon, silicon nanowires and silicon-carbon composite materials, preferably elemental silicon. The particle size of the elemental silicon is preferably 10-800 nm, more preferably 10-400 nm, for example 80-100 nm, 150 nm or 200 nm.

[0021] In the present invention, the mass ratio of the silicon source to the porous niobium oxide may be 100:(0.1-5), preferably 100:(0.5-3), for example 100:1, 100:2, 100:3, 100:4 or 100:5.

[0022] In the present invention, the solid electrolyte is preferably one or more of lithium germanium phosphorus sulfur (LGPS) solid electrolyte, lithium lanthanum zirconium oxide (LLZO) and polymer solid electrolyte. The polymer solid electrolyte is, for example, PEO solid electrolyte powder.

[0023] In the present invention, the mass ratio of the silicon source to the solid electrolyte may be 100:(0.5-5), for example, 100:1, 100:2 or 100:3.

[0024] In the present invention, a solvent is preferably added before the mixing. The solvent is preferably one or more of deionized water, ethanol, methanol, isopropanol and acetone. The mass ratio of the solid electrolyte to the solvent is preferably 1: (0.2-5), for example 1:3 or 1:5.

[0025] In the present invention, the mixing method can be conventional in the art, such as grinding. The mixing is generally carried out under the protection of an inert gas. The mixing time can be 5-30 minutes, such as 10 minutes or 20 minutes.

[0026] In some embodiments, the mixing process preferably includes manual grinding for 5-10 minutes and then ball milling for 5-15 minutes. The rotation speed of the ball milling can be 300-500rpm, such as 400rpm. The ball-to-material ratio in the ball milling process can be (15-25):1, such as 20:1, and the ball-to-material ratio refers to the mass ratio of the grinding ball and the ground material. In the ball milling process, the diameter of a single grinding ball can be 5-15mm, such as 10mm.

[0027] In the present invention, according to the common practice in the art, the mixing generally needs to be dried.

[0028] In the present invention, the chemical formula of the nanoporous lithium titanate oxide is generally Li4Ti n Nb 5-n O 12 , wherein 4≤n≤5. The nanoporous lithium titanate oxide preferably has a spinel lithium titanate structure.

[0029] In a specific embodiment, the nanoporous lithium titanate oxide is Li4Ti 4.5 Nb 0.5 O 12 、Li4Ti5O 12 , or Li4Ti 4.75 Nb 0.25 O 12 .

[0030] In the present invention, the pore size of the nanoporous lithium titanate oxide is preferably 2-10 nm, more preferably 2-5 nm, such as 2.2 nm, 3 nm or 4 nm.

[0031] In the present invention, the method for preparing the nanoporous lithium titanate oxide preferably comprises the following steps:

[0032] (1) mixing a mixed solution containing a lithium source, a titanium source and a niobium source uniformly, drying the mixture, and calcining the mixture at 600-900° C. for 6-24 hours in an air atmosphere to obtain a solid powder;

[0033] (2) The solid powder and the acid solution are mixed for 1-3 hours, centrifuged, washed, dried, and then calcined at 400-800° C. for 3-8 hours in an inert gas atmosphere.

[0034] In step (1) and / or step (2), the mixing method may be conventional in the art, such as stirring or ultrasound.

[0035] In step (1), the mixing time may be 10-30 min, for example 20 min.

[0036] In step (2), the mixing time may be 1-3 h, such as 1.5 h or 2 h.

[0037] In step (1), the lithium source may be one or more of LiNO3, LiCl, CH3COOLi, Li2CO3, LiOH and Li2SO4.

[0038] In step (1), the titanium source may be one or more of tetrabutyl titanate, titanium tetrachloride, titanium isopropoxide and titanyl sulfate.

[0039] In step (1), the niobium source may be one or more of niobium chloride, ammonium niobium oxalate, niobium oxide and niobium ethoxide.

[0040] In step (1), the molar ratio of the titanium source to the niobium source can be weighed according to the chemical formula of the nanoporous lithium titanate oxide in a stoichiometric ratio, for example, 9:1, 1:0 or 19:1.

[0041] In step (1), the ratio of the sum of the amounts of the titanium source and the niobium source to the amount of the lithium source is generally 1:2.

[0042] In step (1), the calcination temperature is preferably 700-800° C., such as 750° C. The calcination time is preferably 8-12 h, such as 10 h.

[0043] In step (2), the acid may be one or more of hydrochloric acid, sulfuric acid and phosphoric acid. The concentration of the acid may be 0.1-1M, such as 0.2M or 0.5M.

[0044] In a specific embodiment, the acid is 0.2 M hydrochloric acid.

[0045] In step (2), the mass ratio of the solid powder to the acid is preferably 1:(30-80), for example 1:50.

[0046] In step (2), the operations and conditions of the centrifugation, washing and drying may be conventional in the art.

[0047] In step (2), the calcination temperature is preferably 500-700°C.

[0048] In the present invention, the carbon source may be one or more of graphite, carbon nanotubes, pyrolytic carbon, amorphous carbon, hard carbon, soft carbon and carbon black.

[0049] In the present invention, the mass ratio of the silicon intermediate product, the nanoporous niobium titanium oxide and the carbon source can be 100:(3-20):(20-110), preferably 100:(5-15):(80-110), for example 100:15:100.

[0050] In the present invention, the preparation method of the mixture of the silicon intermediate product, the nanoporous lithium titanate oxide and the carbon source can be conventional in the art, for example, grinding the silicon intermediate product, the nanoporous lithium titanate oxide and the carbon source for 5-20 minutes.

[0051] In the present invention, the granulation is preferably spray granulation. The operation and conditions of the spray granulation may be conventional in the art. Before the spray granulation, it is generally necessary to first make a mixture of the silicon intermediate product, nanoporous lithium titanate oxide and carbon source into a slurry, and then pump the slurry into a spray granulator for spray granulation. The solvent in the slurry may be one or more of deionized water, ethanol and isopropanol, preferably ethanol. The solid content of the slurry may be 20%-80%, for example 30% or 50%, and the solid content refers to the percentage of the mass of the solid matter in the slurry to the total mass of the slurry. Before the spray granulation, the slurry generally needs to be mixed evenly. The process parameters of the spray granulation may be an air inlet temperature of 170-210°C (for example 190°C) and an air outlet temperature of 110-140°C (for example 120°C).

[0052] The present invention also provides a niobium-titanium-silicon-carbon composite material prepared by the above-mentioned preparation method.

[0053] The present invention also provides a use of the above-mentioned niobium-titanium-silicon-carbon composite material as a negative electrode material in a battery.

[0054] In the present invention, the battery is preferably a lithium ion battery, a sodium ion battery or a solid-state battery.

[0055] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0056] The reagents and raw materials used in the present invention are commercially available.

[0057] The positive and progressive effects of the present invention are:

[0058] The niobium-titanium-silicon-carbon composite material prepared by the present invention has excellent rate performance and first effect, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 TEM image of the porous niobium oxide powder prepared in step (1) of Example 1;

[0060] Figure 2 HRTEM image of the porous niobium oxide powder prepared in step (1) of Example 1;

[0061] Figure 3 TEM image of the nanoporous lithium titanate oxide powder prepared in step (3) of Example 1;

[0062] Figure 4 This is a SEM image of the silicon intermediate product prepared in step (2) of Example 1;

[0063] Figure 5 This is a SEM image of the niobium-titanium-silicon-carbon negative electrode material prepared in Example 1;

[0064] Figure 6 The pore volume-pore size distribution curve (differential) of the porous niobium oxide powder prepared in step (1) of Example 1;

[0065] Figure 7 The pore volume-pore size distribution curve (differential) of the nanoporous lithium titanate oxide powder prepared in step (3) of Example 1;

[0066] Figure 8 XRD patterns of lithium niobate, niobium precursor and porous niobium oxide in step (1) of Example 1;

[0067] Fig. 9 This is the XRD diagram of the nanoporous lithium titanate oxide in step (3) of Example 1. DETAILED DESCRIPTION

[0068] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0069] Example 1

[0070] Step (1): lithium niobate and 1M dilute hydrochloric acid are placed in a reaction kettle at a mass ratio of 20:1, heated to 130°C for reaction for 1 hour, washed with deionized water and dried to obtain a niobium precursor; the niobium precursor is kept at 800°C in an argon gas atmosphere in a tube furnace for 5 hours to obtain porous niobium oxide.

[0071] Step (2): Grind porous niobium oxide, nano-silicon (Cluder 80-100nm), PEO solid electrolyte powder (Cluder E60), and ethanol in a glove box in a mortar at a mass ratio of 5:100:2:10 for 10 minutes, and then put them into a nitrogen-protected agate ball mill with a ball-to-material ratio of 20:1, a single grinding ball diameter of 10mm, and a ball mill speed of 300rpm. Grind for 5 minutes and dry to obtain a silicon intermediate product.

[0072] Step (3): LiNO3, tetrabutyl titanate, and niobium chloride are added to ethanol in a molar ratio of 200:90:10, stirred for 20 minutes, and then dried. After that, the mixture is calcined at 750°C in an air atmosphere for 10 hours to obtain a solid powder. Then, a 0.2M hydrochloric acid solution having a mass of 50 times that of the solid powder is added and stirred for 2 hours. After centrifugation, washing, and drying, the mixture is kept at 500°C in an argon atmosphere for 3 hours to obtain a nanoporous lithium titanate oxide Li4Ti 4.5 Nb 0.5 O 12 .

[0073] Step (4): The silicon intermediate product prepared in step (2), Li4Ti 4.5 Nb 0.5 O 12 2. Artificial graphite (Betray) was evenly ground in a glove box with a mortar at a mass ratio of 100:15:100 for 10 minutes, and then the mixed sample was prepared into a slurry with a solid content of 30% in ethanol and pumped into a spray granulator. Spray granulation was carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C. The slurry was then sieved through a 200-mesh sieve to obtain a niobium-titanium-silicon-carbon composite material.

[0074] Example 2

[0075] Compared with Example 1, except that the mass ratio of porous niobium oxide, nano-silicon, PEO solid electrolyte powder and ethanol in step (2) is changed from 5:100:2:10 to 1:100:2:10, other operations and conditions are the same as those in Example 1.

[0076] Example 3

[0077] Step (1): same as in Example 1;

[0078] Step (2): same as in Example 1;

[0079] Step (3): LiNO3 and tetrabutyl titanate are added to ethanol in a molar ratio of 200:100, stirred for 20 minutes, and then dried. After that, the mixture is calcined at 750°C in an air atmosphere for 10 hours to obtain a solid powder. Then, a 0.2M hydrochloric acid solution with a mass of 50 times that of the solid powder is added and stirred for 2 hours. After centrifugation, washing, and drying, the mixture is annealed at 500°C in an argon atmosphere for 3 hours to obtain a nanoporous lithium titanate oxide Li4Ti5O 12 .

[0080] Step (4): Compared with Example 1, in addition to Li4Ti 4.5 Nb 0.5 O 12 Replaced by Li4Ti5O 12 Except for this, other operations and conditions are the same as those in Example 1.

[0081] Example 4

[0082] Step (1): same as in Example 1;

[0083] Step (2): same as in Example 1;

[0084] Step (3): LiNO3, tetrabutyl titanate, and niobium chloride are added to ethanol in a molar ratio of 200:95:5, stirred for 20 minutes, and then dried. After that, the mixture is calcined at 750°C in an air atmosphere for 10 hours to obtain a solid powder. Then, a 0.2M hydrochloric acid solution with a mass of 50 times that of the solid powder is added and stirred for 2 hours. After centrifugation, washing, and drying, the mixture is kept at 500°C in an argon atmosphere for 3 hours to obtain a nanoporous lithium titanate oxide Li4Ti 4.75 Nb 0.25 O 12 .

[0085] Step (4): In addition to the Li4Ti in Example 1: 4.5 Nb 0.5 O 12 Replaced by Li4Ti 4.75 Nb 0.25 O 12 Except for this, other operations and conditions are the same as those in Example 1.

[0086] Example 5

[0087] Compared with Example 1, except that the PEO solid electrolyte powder in step (2) of Example 1 is replaced by LLTO lithium lanthanum titanium oxide solid electrolyte (Cluder 300nm), other operations and conditions are the same as those in Example 1.

[0088] Example 6

[0089] Compared with Example 1, except that the nano silicon in step (2) of Example 1 is replaced by sand-ground silicon with a particle size of 200 nm (ie, silicon powder is obtained by sand-grinding with an ethanol medium), other operations and conditions are the same as those of Example 1.

[0090] Example 7

[0091] Compared with Example 1, except that the nano-silicon in step (2) of Example 1 is replaced by silicon monoxide (Cruder, 1400), other operations and conditions are the same as those of Example 1.

[0092] Example 8

[0093] Compared with Example 1, except that the nano-silicon in step (2) of Example 1 is replaced by porous carbon-deposited silicon (Cruder, 1800), other operations and conditions are the same as those of Example 1.

[0094] Comparative Example 1

[0095] Step (1): Grind nanosilicon (Cluder 80-100 nm) and ethanol at a mass ratio of 100:10 for 10 min, then put them into a nitrogen-protected agate ball mill with a ball-to-material ratio of 20:1, a single grinding ball diameter of 10 mm, a ball mill speed of 300 rpm, and ball milling for 5 min.

[0096] Step (2): After the product prepared in step (1) and artificial graphite are uniformly ground at a mass ratio of 100:100 for 10 minutes, the mixed sample is prepared into a slurry with a solid content of 30% in ethanol and pumped into a spray granulator. Spray granulation is carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C to obtain a silicon-carbon composite material.

[0097] Comparative Example 2

[0098] Step (1): lithium niobate and 1M dilute hydrochloric acid are placed in a reaction kettle at a mass ratio of 20:1, heated to 130°C for reaction for 1 hour, washed with deionized water and dried to obtain a niobium precursor; the niobium precursor is annealed in a tube furnace at 800°C in an argon gas atmosphere for 5 hours to obtain porous niobium oxide.

[0099] Step (2): Porous niobium oxide, nano silicon (Cluder 80-100nm), PEO solid electrolyte powder (Cluder E60), and ethanol are uniformly ground in a mortar in a glove box at a mass ratio of 5:100:2:10 for 10 minutes, and then placed in a nitrogen-protected agate ball mill, with a ball-to-material ratio of 20:1, a single grinding ball diameter of 10mm, a ball mill speed of 300rpm, ball milling for 5 minutes, and dried to obtain a silicon intermediate product. Step (3): The silicon intermediate product prepared in step (2) and artificial graphite are uniformly ground at a mass ratio of 100:100 for 10 minutes, and the mixed sample is prepared in ethanol into a slurry with a solid content of 30% and pumped into a spray granulator, and spray granulation is performed under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C to obtain a silicon-carbon composite material.

[0100] Comparative Example 3

[0101] Step (1): lithium niobate and 1M dilute hydrochloric acid are placed in a reaction kettle at a mass ratio of 20:1, heated to 130°C for reaction for 1 hour, washed with deionized water and dried to obtain a niobium precursor; the niobium precursor is kept at 800°C in an argon gas atmosphere in a tube furnace for 5 hours to obtain porous niobium oxide.

[0102] Step (2): Grind porous niobium oxide, nano-silicon (Cluder 80-100nm) and ethanol at a mass ratio of 5:100:10 for 10 minutes, then put them into a nitrogen-protected agate ball mill with a ball-to-material ratio of 20:1, a single grinding ball diameter of 10mm, a ball mill speed of 300rpm, ball milling for 5 minutes, and drying to obtain a silicon intermediate product.

[0103] Step (3): Same as in Example 1;

[0104] Step (4): Same as Example 1.

[0105] Comparative Example 4

[0106] Step (1): Grind nanosilicon (Cluder 80-100nm), PEO solid electrolyte powder (Cluder E60) and ethanol at a mass ratio of 100:2:10 for 10 minutes, then put them into a nitrogen-protected agate ball mill with a ball-to-material ratio of 20:1, a single grinding ball diameter of 10mm, a ball mill speed of 300rpm, ball milling for 5 minutes, and drying to obtain a silicon intermediate product.

[0107] Step (2): LiNO3, tetrabutyl titanate, and niobium chloride were added to ethanol in a molar ratio of 200:90:10, stirred and dried, and then calcined at 750°C in air for 10 hours to obtain a solid powder, and then a 0.2M hydrochloric acid solution with a mass of 50 times that of the solid powder was added and stirred for 2 hours. After centrifugation, washing, and drying, the solid powder was annealed at 500°C in an argon atmosphere for 3 hours to obtain Li4Ti 4.5 Nb 0.5 O 12 .

[0108] Step (3): The silicon intermediate product prepared in step (2), Li4Ti 4.5 Nb 0.5 O 12 2. Artificial graphite (Betray) was evenly ground in a glove box with a mortar at a mass ratio of 100:15:100 for 10 minutes, and then the mixed sample was prepared into a slurry with a solid content of 30% in ethanol and pumped into a spray granulator. Spray granulation was carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C. The slurry was then sieved through a 200-mesh sieve to obtain a niobium-titanium-silicon-carbon composite material.

[0109] Effect Example

[0110] (1) Morphology and pore size characterization

[0111] Figure 1 and Figure 2 The TEM image and HRTEM image of the porous niobium oxide powder prepared in step (1) of Example 1 are respectively Figure 1 It can be seen that the pore size is between 2-3nm. Figure 2 Obvious defect structures can be seen in the marked area; Figure 3 This is a TEM image of the nanoporous lithium titanate oxide powder prepared in step (3) of Example 1. It can be seen from the image that the pore size is between 2-3 nm; Figure 4 This is a SEM image of the silicon intermediate product prepared in Example 1; Figure 5 This is a SEM image of the niobium-titanium-silicon-carbon negative electrode material prepared in Example 1. Figure 6 and Figure 7 The pore size test results show that the pore size of the porous niobium oxide powder prepared in step (1) of Example 1 is 2.4162 nm, and the pore size of the nanoporous lithium titanate oxide powder prepared in step (3) of Example 1 is 2.2548 nm; Figure 8 The XRD diagram of lithium niobate, niobium precursor, and porous niobium oxide in step (1) of Example 1, wherein the niobium precursor is niobic acid obtained by completely exchanging hydrogen ions of lithium niobate with lithium ions in hydrochloric acid; Fig. 9 This is the XRD diagram of the nanoporous lithium titanate oxide in step (3) of Example 1. It can be seen from the figure that it is a spinel lithium titanate structure.

[0112] (2) Lithium-ion battery electrochemical performance test

[0113] The niobium-titanium-silicon-carbon composite materials prepared in Examples 1 to 8 and the silicon-carbon composite materials prepared in Comparative Examples 1-4 were subjected to half-cell tests. The test method is: the above materials are uniformly mixed with a binder CMC (sodium carboxymethyl cellulose) and conductive carbon black in a mass ratio of 80:10:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 80°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using a 1 mol / L LiPF6 electrolyte (the solvent is EC, DMC and FEC, EC:DMC=1:1 (volume ratio), and FEC accounts for 5% of the total volume of the solvent), a polypropylene microporous membrane as a diaphragm, and a metal lithium sheet as a counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 25°C and a charge and discharge voltage range of 0.01 to 1.5V (1C=1000mAh g -1 ), the test results are shown in Table 1.

[0114] Table 1

[0115]

[0116]

[0117] According to the above experimental results, the niobium-titanium-silicon-carbon composite material prepared in the present invention has excellent high-rate specific capacity and cycle performance.

[0118] By comparing Example 1 with Comparative Example 1, it can be found that the silicon-carbon composite material prepared in Comparative Example 1 has poor ion conductivity of the overall sample, and lithium ions are difficult to fully deintercalate, because the raw materials are not coated with porous niobium oxide, niobium titanium oxide and solid electrolyte, so the specific capacity and cycle life at 10C are poor. By comparing Example 1 with Comparative Example 2, it can be found that the silicon-carbon composite material prepared in Comparative Example 2 will reduce the partial ion conductivity of graphite and silicon due to the lack of niobium titanium oxide coating, so the 10C rate capacity and cycle life are significantly reduced. By comparing Example 1 with Comparative Example 3, it can be seen that due to the lack of solid electrolyte, Comparative Example 3 cannot construct an ion transmission path between the coating material and silicon, which reduces the partial ion conductivity, and thus affects the rate performance. By comparing Example 1 with Comparative Example 4, it can be seen that due to the lack of porous niobium oxide, Comparative Example 4 cannot construct a high-rate lithium storage channel on the silicon surface, and cannot inhibit silicon expansion, so it has a greater impact on high-rate lithium storage.

[0119] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a niobium-titanium-silicon-carbon composite material, characterized in that: The steps include: Porous niobium oxide, a silicon source and a solid electrolyte are mixed to obtain a silicon intermediate product; then the mixture of the silicon intermediate product, nanoporous lithium titanate oxide and a carbon source is granulated and sieved to obtain the niobium-titanium-silicon-carbon composite material.

2. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The preparation method meets one or more of the following conditions: (1) The chemical formula of the porous niobium oxide is Nb2O 5-x , where 0≤x<1; (2) The pore size of the porous niobium oxide is 1-15 nm, preferably 2-5 nm, such as 2.4 nm, 3 nm or 4 nm; (3) The silicon source is one or more of elemental silicon, silicon monoxide, silicon dioxide, silicon alloy, porous silicon, silicon nanowires and silicon-carbon composite materials, preferably elemental silicon; the particle size of the elemental silicon is preferably 10-800 nm, more preferably 10-400 nm; (4) The mass ratio of the silicon source to the porous niobium oxide is 100:(0.1-5), preferably 100:(0.5-3), for example, 100:1, 100:2, 100:3, 100:4 or 100:

5.

3. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The preparation method meets one or more of the following conditions: (1) The solid electrolyte is one or more of a lithium germanium phosphorus sulfur solid electrolyte, a lithium lanthanum zirconium oxide and a polymer solid electrolyte; the polymer solid electrolyte is, for example, a PEO solid electrolyte powder; (2) The mass ratio of the silicon source to the solid electrolyte is 100:(0.5-5), for example, 100:1, 100:2 or 100:3; (3) A solvent needs to be added before the mixing; the solvent is preferably one or more of deionized water, ethanol, methanol, isopropanol and acetone; the mass ratio of the solid electrolyte to the solvent is preferably 1: (0.2-5), for example 1:3 or 1:5; (4) The mixing time is 5-30 min.

4. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the porous niobium oxide comprises the following steps: (a) subjecting a mixture of lithium niobate and an acid to a hydrothermal reaction at 110-150° C. for 1-5 hours, washing and drying to obtain a niobium precursor; (b) calcining the niobium precursor at 400-900° C. for 0.5-6 h under inert gas protection to obtain the porous niobium oxide; Wherein, the acid is preferably one or more of hydrochloric acid, sulfuric acid and phosphoric acid; the concentration of the acid is preferably 0.5-2M; the mass ratio of the lithium niobate and the acid is preferably (10-30):

1.

5. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The preparation method meets one or more of the following conditions: (1) The chemical formula of the nanoporous lithium titanate oxide is Li4Ti n Nb 5-n O 12 , where 4≤n≤5; (2) The pore size of the nanoporous lithium titanate oxide is 2-10 nm, preferably 2-5 nm, such as 2.2 nm, 3 nm or 4 nm; (3) The nanoporous lithium titanate oxide has a spinel lithium titanate structure; (4) The carbon source is one or more of graphite, carbon nanotubes, pyrolytic carbon, amorphous carbon, hard carbon, soft carbon and carbon black; (5) The mass ratio of the silicon intermediate product, the nanoporous niobium titanium oxide and the carbon source is 100:(3-20):(20-110), preferably 100:(5-15):(80-110), for example 100:15:

100.

6. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The preparation method of the nanoporous lithium titanate oxide comprises the following steps: (1) mixing a mixed solution containing a lithium source, a titanium source and a niobium source uniformly, drying the mixture, and calcining the mixture at 600-900° C. for 6-24 hours in an air atmosphere to obtain a solid powder; (2) The solid powder and the acid solution are mixed for 1-3 hours, centrifuged, washed, dried, and then calcined at 400-800° C. for 3-8 hours in an inert gas atmosphere.

7. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 6, characterized in that: The preparation method of the nanoporous lithium titanate oxide meets one or more of the following conditions: (1) In step (1), the mixing time is 10-30 min; (2) In step (2), the mixing time is 1-3 hours; (3) The lithium source is one or more of LiNO3, LiCl, CH3COOLi, Li2CO3, LiOH and Li2SO4; (4) The titanium source is one or more of tetrabutyl titanate, titanium tetrachloride, titanium isopropoxide and titanyl sulfate; (5) The niobium source is one or more of niobium chloride, ammonium niobium oxalate, niobium oxide and niobium ethoxide; (6) The molar ratio of the titanium source to the niobium source can be weighed according to the chemical formula of the nanoporous lithium titanate oxide in a stoichiometric ratio, for example, 9:1, 1:0 or 19:1; (7) The ratio of the sum of the amounts of the titanium source and the niobium source to the amount of the lithium source is 1:2; (8) In step (2), the acid is one or more of hydrochloric acid, sulfuric acid and phosphoric acid; the concentration of the acid is preferably 0.1-1M; (9) In step (2), the mass ratio of the solid powder to the acid is 1:(30-80), for example 1:

50.

8. The method for preparing the niobium-titanium-silicon-carbon composite material according to claim 1, characterized in that: The granulation is spray granulation; Before the spray granulation, it is preferred that the mixture of the silicon intermediate product, nanoporous lithium titanate oxide and carbon source is first made into a slurry, and then the slurry is pumped into a spray granulator for spray granulation; the solvent in the slurry is preferably one or more of deionized water, ethanol and isopropanol; the solid content of the slurry is preferably 20%-80%, for example 30% or 50%; The process parameters of the spray granulation are preferably an air inlet temperature of 170-210°C and an air outlet temperature of 110-140°C.

9. A niobium-titanium-silicon-carbon composite material prepared by the method for preparing a niobium-titanium-silicon-carbon composite material according to any one of claims 1 to 8.

10. Use of the niobium-titanium-silicon-carbon composite material as claimed in claim 9 as a negative electrode material in a battery.

Citation Information

Cited By

  • Niobium-based compound / silicon carbon composite material and preparation method and application thereof

    CN121641926A